Multiple system degeneration with glutamate dehydrogenase deficiency: pathology and biochemistry. Issue 12 (December 1990) - Chokroverty, S; Nicklas, W; Miller, D C; Goldberg, J; Choe, J; Banner, C; Thomas, J; Duvoisin, R
Abstract : The neuropathological findings in a patient with antemortem diagnosis of olivopontocerebellar atrophy (OPCA) and reduced leucocytic glutamate dehydrogenase (GDH) activity included cerebellar cortical degeneration, most marked in the superior vermis, mild atrophy of the pons and the inferior olivary nucleus, marked reduction of anterior horn cells at all levels and gliosis in both lateral columns. GDH activities and their thermolability in "soluble" and "particulate" fractions in the cerebral cortex, cerebellar hemisphere and vermis were not significantly different from the values in two control brains. GDH mRNA in the patient's brain was not altered in size or amount.